Gendering Spanish democracy - Threlfall, Mónica.; Cousins, Christine, 1943-; Valiente Fernández, Celia (London ; New York : Routledge, 2005)
Addressing aspects of women's experience such as the public spheres of elective politics, public policy-making & the labour market, this book offers an up-to-date critical assessment of gender in Spain.
pt. 1. Gendering democratic Spain -- pt. 2. Engendering new policies -- pt. 3. Changing gender relations?
Includes bibliographical references and indexes.
"Bibliographical commentary and bibliography of research on gender in Spanish history, politics, public policy, sociology, anthropology and ethnography since the 1920s, published in English (1971-2002) ": pages 220-230
Print version record.
eBooks on EBSCOhost
Keywords: Sex discrimination -- Government policy -- Spain; Sex role -- Spain; Discrimination sexuelle -- Politique gouvernementale -- Espagne; Rôle selon le sexe -- Espagne; SOCIAL SCIENCE -- Feminism & Feminist Theory; Sex discrimination -- Government policy; Sex role; Spain